Nursing Students’ Experience of Medication Errors and Its Related Factors: A Questionnaire-Based Study: Nursing Students experience of medication errors - Rezaee, Serva; Vahedi, Shiva; Nouri, Bijan; Valiee, Sina (Advances in Nursing & Midwifery, 2021)
Abstract Introduction: Providing safe care is one of the nursing goals and medication errors are considered as one of the threatening factor for patient safety. The aim of this study was to determine the nursing students’ experience of medication errors and its related factors. Methods: This descriptive cross-sectional study was conducted on 120 nursing students, from third to eighth semester, in Kurdistan University of Medical Sciences, Iran, enrolled through the census. Data collection was performed using a three-part questionnaire including demographic features, types of medication errors and its causes. Data were analyzed through using descriptive statistics, Chi-square, Fisher’s exact test, and correlation coefficient. Results: The average number of student medication errors in the past semester was 20 (16.4%), in which 16 (13.1%) of them reported their errors. The most common types of medication errors was errors in determining the type of medication (66.4%, n=81). Also, the most common cause of medication errors in the viewpoints of nursing students were the lack of pharmacological information among students (83.1%, n=102), illegibility of drug orders (76.3%, n=93) and distraction (73.8%, n=90). Conclusions: Based on the findings of this study, effective clinical and theoretical pharmacological educations are essential for increasing the pharmaceutical information of the students in order to reduce the amount of medication errors. It is necessary to increase the pharmacological information of nursing students by organizing various pharmacological workshops and giving time to students from training and internship to pharmaceutical conferences.